Makna Tradisi Marariq Masyarakat Bangsawan Suku Sasak Di Lombok - Ahmad Khaerul Kholidi; Adi Faizun; Lalu Muhammad Iqbal; Ahmad Ramdhani (Institut Agama Islam Negeri Palopo, 2021)
The background of this research is the culture of marriage as a form of expression of life as stated in traditional ceremonial processions, especially the Sasak tribe in Lombok. The tradition of merarik has become part of a wedding ceremony for the Sasak people, which is a procession carried out by a pair of grooms and brides to conduct a wedding. The customary process is related to behavior patterns, which is a reflection of the meaning of community behavior, if it is violated, there will be disharmony in social life. In addition, pulling in essence can be interpreted as an important marriage in human life. Each custom process merarik in society Sasak-meal contained specific meaning in it. Therefore, thistradition merarik deserves to be appointed as a research subject, especially in its unique aspects, why thetradition is merarik used as a mandatory ritual to be fulfilled. Merariq is wedding rituals carried out by the Sasak people on the island of Lombok. Merariq for the people of Lombok is half of life to start a new life through the marriage process. Merariq has a different ritual than other regions in Indonesia. The Sasak tribe community consists of two differences in social caste, including those with blue blood, such as: the names Lalu, Lale, Baiq, Raden, Mamiq, while those who do not have royal blood are usually calledchildren amaq, with differences in hereditary caste which will affect the lifestyle. both in the implementation of wedding rituals, for example in the marriage process, it will feel thick with cultural nuances.